2005
DOI: 10.1111/j.1399-543x.2005.00120.x
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic exercise capacity in normal adolescents and those with type 1 diabetes mellitus

Abstract: Adolescent patients with T1DM showed a reduced aerobic exercising capacity when compared to healthy peers matched to anthropometric conditions. This potential condition should be taken into consideration by the time of evaluation of the aerobic performance of these patients with glycemic control level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
99
4
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(114 citation statements)
references
References 22 publications
(20 reference statements)
9
99
4
2
Order By: Relevance
“…The decreased exercise capacity of Akita mice observed in this study is supported by previous work in rodent models of T1D (26,27) as well as in human subjects with T1D (28)(29)(30)(31). Although the precise cause for this diminished capacity remains controversial, a number of factors are thought to contribute to this decline (30,31).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The decreased exercise capacity of Akita mice observed in this study is supported by previous work in rodent models of T1D (26,27) as well as in human subjects with T1D (28)(29)(30)(31). Although the precise cause for this diminished capacity remains controversial, a number of factors are thought to contribute to this decline (30,31).…”
Section: Discussionsupporting
confidence: 87%
“…Fibers were fixed immediately after isolation (referred to as Control fibers) or placed in culture dishes with plating media (10% normal horse serum, 0.5% chick embryo extract in DMEM) overnight (18 h; referred to as Activated fibers). For all single-fiber experiments, the minimum and maximum number of fibers analyzed is provided in a range (i.e., [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] and is derived from at least three mice per experimental group.…”
Section: Single Muscle Fiber Isolationmentioning
confidence: 99%
“…Many studies have noted pulmonary gas transfer limitations in subjects with type 1 diabetes who are of average or belowaverage fitness at rest (Benbassat et al 2001;Britton 1988;Cooper et al 1990;Fuso et al 1996;Innocenti et al 1994;Ramirez et al 1991;Sandler et al 1986;Strojek et al 1992;Villa et al 2004;Weir et al 1988) and in type 1 diabetic subjects who are of average fitness during exercise (Hsia and Raskin 2005;Komatsu et al 2005;Ljubic et al 1998;Niranjan et al 1997). However, the exact mechanism for this gas diffusion limitation, reductions in D M or decrements in V C has not been elucidated.…”
mentioning
confidence: 94%
“…Various authors have demonstrated that, during the incremental exercise test, type 1 diabetic patients have a peak of oxygen uptake (VO2-peak), which is lower than in healthy controls [82,83]. The VO2-peak indicates the maximum amount of oxygen that can be used by an individual during a physical activity involving large muscle groups.…”
Section: Cardiopulmonary Exercise Testmentioning
confidence: 99%